Implementasi Kebijakan Undang-Undang Perkawinan Di Kecamatan Balaesang Kabupaten Donggala - Emiyanti; Rivai, Abdul; Farista, Gita (JPS: Journal of Publicness Studies, 2025)
This research aims to explore how the implementation of the Marriage Law policy, particularly regarding the minimum age for marriage as stipulated in Law Number 16 of 2019, in Balaesang Sub-District. The study employs George Edward III’s policy implementation model, which includes four aspects: Communication, resources, disposition, and bureaucratic structure.This study uses A qualitative method with a descriptive approach. Informants were selected using Purposive, totaling seven individuals. The types of data used are primary and Secondary data. Data collection techniques included interviews, documentation, And observation.The research findings indicate that the implementation of the minimum Marriage age policy at the KUA of Balaesang has been carried out in accordance With procedures, but it still faces several challenges. Communication related to The dissemination of policy to the community remains uneven, resulting in low Public legal awareness and understanding. The availability of resources is still Limited and inadequate. The disposition of the implementers is relatively good. However, the effectiveness of the bureaucratic structure is still influenced by the Lack of coordination with external parties. Therefore, there is a need to enhance Equal dissemination, strengthen resource capacity, and improve inter-agency Coordination to realize optimal policy implementation in preventing underage Marriage in Balaesang Sub-District